Working with children of alcoholics the practitioner's handbook - Robinson, Bryan E.; Rhoden, J. Lyn.; Sage eBooks (Thousand oaks, [Calif.] ; London : SAGE, 1998)
An examination of the effects of alcoholism on essential family processes and the place of alcoholism in a larger cultural context are included in this book. The authors also address children's academic performance and behavioural problems.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children of alcoholics -- Counseling of -- United States; Social work with children -- United States; Electronic books